1991
DOI: 10.1017/s0007485300051208
|View full text |Cite
|
Sign up to set email alerts
|

The concentration of lamdacyhalothrin and its effect on the cutworm Agrotis segetum (Lepidoptera: Noctuidae)

Abstract: During initial screening of the synthetic pyrethroid lamdacyhalothrin (PP 321) at a concentration of 44 and 22 mg/1 and applied as a 30 ml drench over each plant against third to fourth instar cutworms, Agrotis segetum (Denis & Schiffermuller) in microplots, few died but they did not damage the plants.Reducing the concentrations to 11 and 5.5 mg/1 increased mortality and plant damage. When A. segetum were confined on soil treated with the insecticide at concentrations of 22, 11 and 5.5 mg/1 and sprayed at an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In view of successful control of potato mirids in the cage experiment, however, further investigation of lambda-cyhalothrin is warranted and it may be that higher concentrations are required to control potato mirids in the field. Blair (1991) found that high concentrations of lambda-cyhalothrin appeared to have a repellent and/or antifeedant effect on insects. This may have been partly responsible for higher mortality in the cages than in the field trial.…”
Section: Discussionmentioning
confidence: 98%
“…In view of successful control of potato mirids in the cage experiment, however, further investigation of lambda-cyhalothrin is warranted and it may be that higher concentrations are required to control potato mirids in the field. Blair (1991) found that high concentrations of lambda-cyhalothrin appeared to have a repellent and/or antifeedant effect on insects. This may have been partly responsible for higher mortality in the cages than in the field trial.…”
Section: Discussionmentioning
confidence: 98%
“…Lambda-cyhalothrin has a repellancy and/or antifeedant effect on insects (Blair 1991). The long-term residual effect (up to 34 DAT for ACM) of lambda-cyhalothrin makes it a versatile insecticide that can either be applied as a curative or preventative control for ACM.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports of gonandromorphism from 18families in this order. Among them, a lot of specimens have been reported for butterfly species (e.g., in Geometridae, Lycaenidae, Nymphalidae, Pieridae, Papilionidae) [3,[10][11][12][13][14][15] and also for moths (e.g., Noctuidae) [16,17]. However, the Papilionidae, Pieridae, and Saturniidae families account for the majority of cases [9].…”
Section: Introductionmentioning
confidence: 99%